Hydroxychloroquine as Oral Antidiabetic Agent During Coronavirus Pandemic - Anirban Majumder (Global Journal of Infectious Diseases and Clinical Research - Peertechz Publications, 2020)
The coronavirus disease 2019 (COVID-19) is spreading rapidly. Hydroxychloroquine (HCQ), an old drug for treatment of malaria and autoimmune disease with acceptable safety, has shown promising but yet unproven effect against COVID-19 infection. HCQ is an approved agent by the Drug Controller General of India (DCGI) for the therapy of Type 2 Diabetes. In view of the fact that people with diabetes face higher chance of experiencing serious complications from COVID-19, HCQ may have preferential position as an antidiabetic agent during this crisis period.